Beginning Hibernate 2nd Edition - Linwood, Jeff (Apress, 2012)
Hibernate is an amazing piece of software. With a little experience and the power of annotations, you can build a complex, database-backed system with disturbing ease. Once you have built a system using Hibernate, you will never want to go back to the traditional approaches. While Hibernate is incredibly powerful, it presents a steep learning curve when you first encounter it—steep learning curves are actually a good thing because they impart profound insight once you have scaled them. Yet gaining that insight takes some perseverance and assistance. Our aim in this book is to help you scale that learning curve by presenting you with the minimal requirements of a discrete Hibernate application, explaining the basis of those requirements, and walking you through an example application built using to them. We then provide additional material to be digested once the fundamentals are firmly understood. Throughout, we provide examples, rather than relying upon pure discourse. We hope that you will continue to find this book useful as a reference text long after you have become an expert on the subject